Effects of Color, Scouring Method, and Age on the Visual Sensibility of Naturally Colored Organic Cotton (NaCOC). Issue 3 (27th June 2012) - Park, Jangwoon; Chang, Yoon; Hong, Wongi; Lee, Myungeun; Han, Ahreum; Chae, Youngjoo; Cho, Gilsoo; You, Heecheon
Abstract In parallel to the social trend of green consumerism and well‐being, the demand for naturally colored organic cotton (NaCOC) continually increases in the textile and clothing industry. The present study examined the effects of NaCOC color, scouring method, and age on the visual sensibility of NaCOC. Two age groups (20s and 30s; 40s and 50s) of women rated three color sets of NaCOC specimens (ivory, green, and coyote brown) treated by two chemical scouring methods (Na2CO3 and NaOH) and two bioscouring methods (enzyme and boiling water) using 7‐point scales of nine visual sensibilities (bright‐dark; clear‐murky; heavy‐light; vivid‐subdued; warm‐cool; fresh‐stale; strong‐weak; showy‐plain; and luxurious‐cheap). Preferred scouring methods by NaCOC color and/or age group were recommended for each visual sensibility (e.g., preferred scouring methods for fresh sensibility are Na2CO3 for ivory NaCOC, Na2CO3 and NaOH for green NaCOC, and boiling water for coyote brown NaCOC). In addition, the representative visual sensibilities of each NaCOC color (e.g., those of coyote brown NaCOC are dark, murky, heavy, vivid, warm, stale, strong, plain, and luxurious sensibilities) were identified for the women participants. Last, it was demonstrated that a bioscouring method can replace the traditional chemical methods for selected visual sensibilities (e.g., boiling water for luxurious sensibility). © 2012 Wiley Periodicals, Inc.